2015
DOI: 10.1080/13657305.2015.994236
|View full text |Cite
|
Sign up to set email alerts
|

Price Transmission in Thai Aquaculture Product Markets: An Analysis Along Value Chain and Across Species

Abstract: & We have examined the presence of price transmission asymmetry along the value chain, and the price transmission across four main aquaculture species in Thai fish market using monthly data from January 2001 to October 2010. This is an attempt to contribute to the literature on horizontal and vertical price transmission in the seafood markets including the price transmission asymmetry in the developing countries. We did not find any evidence of asymmetric price transmission in walking catfish (except in long-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
2
9
1
Order By: Relevance
“…Importantly, a study by Barahona et al (2014) identified asymmetric price transmission in the pork industry, but price transmission appeared to be symmetric in the poultry industry. In contrast, Singh et al (2015) did not find any evidence of asymmetric price transmission in fish markets. Nonetheless, Ghoshray (2008) found that adjustment to the long-run equilibrium is relatively faster when the price differential is negative in rice markets.…”
Section: Literature Reviewcontrasting
confidence: 59%
See 1 more Smart Citation
“…Importantly, a study by Barahona et al (2014) identified asymmetric price transmission in the pork industry, but price transmission appeared to be symmetric in the poultry industry. In contrast, Singh et al (2015) did not find any evidence of asymmetric price transmission in fish markets. Nonetheless, Ghoshray (2008) found that adjustment to the long-run equilibrium is relatively faster when the price differential is negative in rice markets.…”
Section: Literature Reviewcontrasting
confidence: 59%
“…The issue of asymmetric price transmission in the palm oil sector of the Thai economy has not been thoroughly studied. Previous studies on asymmetric price transmission in the Thai economy were regarding the livestock industry (Barahona, Trejos, Lee, Chulaphan, & Jatuporn, 2014), aquaculture products (Singh, Dey, Laowapong, & Bastola, 2015), rice export prices (Ghoshray, 2008), and macroeconomic indicators (Rafiq, Salim, & Bloch, 2009). Importantly, a study by Barahona et al (2014) identified asymmetric price transmission in the pork industry, but price transmission appeared to be symmetric in the poultry industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar results were reported by Macfadyen et al [6] who found that farmed tilapia prices decreased with increasing supply to the market from September to December and prices increased in March and April as supplies declined at that time of the year. Similarly, many authors have reported that fish prices are demand driven [21,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Reference [12] and [13] studied fish price elasticity and transmission between wholesaler and retailer, and concluded that changes in wholesale prices were greater for retail price increases than for retail price decreases. Market interactions between farmed fish and the wild fish have been studied in many countries [14][15][16][17][18][19][20][21]. None of previous studies investigated cointegration of farmed fresh fish with wild frozen fish in the main Egyptian wholesale market.…”
Section: Introductionmentioning
confidence: 99%
“…This article investigates price transmission for two wild species (cod and Alaska Pollock) and one farmed species (salmon). Price transmission has been an important topic in this journal in recent years (Asche, Dahl, Valderrama, & Zhang, 2014;Pincinato & Asche, 2016;Singh, 2016), including a special issue on the topic (Fernández-Polanco & Llorente 2015; Gordon & Hussain, 2015;Gordon & Maurice, 2015;Singh, Dey, Laowapong, & Bastola, 2015;Tveteras, 2015). The current article takes on an insight from the hedonic price literature where Asche, Larsen, Smith, Sogn-Gruntvåg, and Young (2015) indicated that prices vary by retail chain.…”
mentioning
confidence: 99%